Unraveling the Evolutionary Patterns of Genus Frontonia: An Integrative Approach with Morphological and Molecular Data - Ratih Kusuma Wardani; Ragib Ahsan; Mann Kyoon Shin (Biology)
Ciliates of the genus Frontonia have been extensively studied to resolve their phylogenetic and evolutionary history, but challenges remain. This study used molecular analyses of SSU rRNA genes, phylogenetic tree reconstruction, molecular dating, and diversification analysis, together with ancestral state reconstruction of morphological traits and habitat preferences. Data included newly sequenced Korean species, GenBank records and published morphological information. Phylogenetic trees revealed paraphyly within Frontonia, identifying four groups that emerged in the Mesozoic era: Group I (~172 mya), Group II (~83 mya), Group III (~115 mya), and Group IV (~190 mya), with a common ancestor dating to ~420 mya in the Palaeozoic era. Diversification analysis revealed higher extinction rates (0.826 and 0.613 species/year) than speciation rates (0.011 and 0.016 species/year). Morphological evolution showed habitat adaptation and plasticity, with habitat transitions unrelated to contractile vacuolar traits. The SSU rRNA gene polymorphism likely contributed to the paraphyletic state of Frontonia. These results highlight the complex evolutionary patterns of the genus, shaped by genetic diversity, morphology, and environmental constraints.